Centre d'Art Contemporain Fri-Art Kunsthalle 1996. - Müller, Grégoire; Ritter, Michel; Fri-Art Centre d'Art Contemporain Kunsthalle, Fribourg (Fribourg : FRI-ART Centre d'Art Contemporain - Kunsthalle, 1996)
Müller, Claudia & Julia ; Martin, Marie-France & Patricia ; Green, Renée ; Gonzalez-Foerster, Dominique ; Bernardini, Alain ; Epars, Ariane ; Franke, Manuel ; Hoffmann, Leni ; Schuler, Horst ; Beecroft, Vanessa ; Scher, Julia ; Paradeis, Florence ; Neshat, Shirin
Engels & Frans
boek